(untitled) (Bangladesh Veterinarian, 2012)
Structure and postnatal development of vagina in 21 ISA brown chickens was studied at three, 23 and 46 weeks of age. At 3 weeks of age the vagina was narrower and thicker then the uterus. The undifferentiated wall of vagina consisted of low primary mucosal folds lined by simple columnar epithelium to a pseudostratified ciliated columnar epithelium and a connective tissue layer underneath. At three weeks of age, scattered smooth muscle fibres were in the subepithelial connective tissue layer. Rapid structural changes occurred at 23 weeks of age in the adult bird, mucosal folds were narrowed and tongue-shaped. Lamina propia was devoid of glands and contained lymphocytes. Tunica muscularis was well developed at 23 and 46 weeks. DOI: http://dx.doi.org/10.3329/bvet.v28i2.10676 Bangl. vet. 2011. Vol. 28, No. 2, 75 79